Potential drivers of leprosy infection: A case–control study of parasitic coinfection and water, sanitation, and hygiene in North Gondar, Ethiopia - Wasson, Megan K.; Whitson, Cassidy; Miller, Bridget; Abebe, Wondwossen; Tessema, Belay; Emerson, Lisa E.; Anantharam, Puneet; Tesfaye, Annisa Befekadu; Fairley, Jessica K. (Frontiers in Tropical Diseases, 2022)
Background Despite extensive control measures and a declining number of human reservoirs, the incidence of leprosy in excess of 200,000 new cases each year suggests that alternative pathways of transmission may play a role in continued endemicity. Parasitic coinfection and limited water, sanitation, and hygiene (WASH) have been suggested to predispose individuals to Mycobacterium leprae infection and were further explored in this study. Methods Leprosy cases and uninfected controls were recruited from areas around North Gondar, Ethiopia throughout 2019. Participants completed dietary and WASH surveys in addition to providing stool for helminth microscopic diagnosis and urine for Schistosoma mansoni Point-of-care circulating cathodic antigen (POC-CCA)™ rapid diagnostic testing. A similar methodology was employed for a case–control study of leprosy previously conducted by our research team in North Gondar from May to October of 2018. To more comprehensively evaluate associations between the above exposures and leprosy, data from the present 2019 study and the previous 2018 study were combined in select multivariate logistic regression analyses. Results A total of 47 men (59%) and 33 women (41%) participated in this study with an average age of 40 (SD 15.0 years). Most leprosy cases were multibacillary (93%). There was a high prevalence of parasitic coinfection among both cases (71%) and controls (60%). WASH insecurities were also widespread. On multivariate analysis, lack of soap for handwashing [aOR= 2.53, 95% CI (1.17, 5.47)] and the lack of toilet facilities [Adjusted odds ratio (aOR)= 2.32, 95% CI (1.05, 5.12)] were significantly associated with leprosy. Positive directionality was identified for a number of other inputs, including helminth infection [aOR= 3.23, 95% CI (0.85, 12.35)]. Conclusions Taken together, these findings strengthen previous research conducted in 2018 implicating poor WASH conditions as a driver of leprosy infection. Leprosy remains the leading infectious cause of disability in the world. As such, future research should explore the above susceptibilities in more depth to curtail the global burden of disease.